PENELITIAN PEMBUATAN POLI METIL METAKRILAT - Wahyuni, Dwi; Dewi, Sri Rukmini (BRIN Publishing, 2003)
The poly methyl methacrylate (PMMA) research has been excecuted. Methyl methacrylate is polymerized by the free radical inisiation with the suspension condition using benzoyl peroxyde inisiator, water as a solution and the gelatine stabilizer, in this reseaarch is executed as a standard ratio (part per part:monomer : water : stabilizer = 100 : 350 : (0.1 1) with the inisiator to monomer ratio variation (part per part) are: 0.1 per 50; 0,175 per 50; 0,25 per 50; 0,25 per 50, the temperature variation are : 30 degree C, 45 degree C, 60 degree C and the time polymerization until 320 minutes. The result showed that the optimum monomer polymerizeation was at the inisiator to monomer ratio 0,25 per 50, the temperature at 45 degree C and at the time polymerization until 300 minutes with the monomer conversion was 86 percent. The Infra Red Spectroscopy analyses showed that there are poly methyl methacrylate in the product. The Gas Liquid Chromatography analysis showed the evolution of the monomer (methil methacrylate concetration.